Rain attenuation prediction model for tropical V-band satellite earth link - Khairayu, Badron; Ismail, Ahmad Fadzil; Islam, Md. Rafiqul; Abdul Rahman, Tharek; Din, Jafri (2011)
Radiowave propagation plays a very important part in the design and eventually dictates performance of space communication systems. The requirements of today’s satellite communication have grown extensively where higher capacity communications systems are needed. The escalating demands for microwave and millimetre wave communications are causing acute frequency spectrum congestion. Hence, existing and future satellite system operators are planning to employ frequency bands as high as the V-band. The challenge in operating at such high frequencies for communication purposes is that there exist stronger electromagnetic interaction between the radio signals and atmospheric hydrometeors. These instances will without doubt degrade the performance of such high frequency satellite communication systems. The development of a model capable of accurately predicting the V-band signal propagation is considered very important particularly for systems operating in tropical region. Researchers and engineers alike can employ the model to estimate the availabilities of effectively the future high frequencies satellite services.